(untitled) (Research, Society and Development, 2022)
The human airway is a system composed of important anatomical structures that protect and maintain permeability. This paper aims to present airway clearance and access maneuvers in emergency situations. A literature review was carried out by searching the Scielo and Embase databases. For this, we used descriptors "Airway Obstruction" and "Emergency" and "Dentistry" with 40 articles screened. In basic maneuvers, the Heimlich maneuver consists of infradiaphragmatic compression in an “L” shape. The Jaw Thrust maneuver is characterized by the protrusion of the jaw, while the Chin Lift involves cervical hyperextension and mental elevation. In advanced maneuvers, Endotracheal Intubation ensures airflow in the airways through the placement of an oral or nasal cannula. Cricothyroidotomy is an invasive procedure that creates an opening through the cricothyroid membrane, while the Tracheostomy is a surgical procedure to create an opening between the 2nd and 3rd tracheal ring. Therefore, the Heimlich maneuver is chosen as the first alternative in situations of acute obstruction, followed by the Jaw Thrust, Chin Lift and Endotracheal Intubation maneuvers. Cricothyroidotomy is the invasive procedure of first choice for reestablishing ventilation in emergency situations, while tracheostomy, which is elective, requires longer procedure time. Therefore, the acute obstruction of the upper airways is a serious and emergency complication, so the dentist must be prepared to quickly reverse this condition in these situations.